PENGARUH PENDIDIKAN KEWIRAUSAHAAN, LINGKUNGAN KELUARGA DAN MOTIVASI TERHADAP MINAT BERWIRAUSAHA (STUDI KASUS MAHASISWA MANAJEMEN 2018-2021) - Febiola; Yesi Gusteti; Eka Ermawati (MANAJEMEN DEWANTARA, 2022)
The purpose of this study was to determine how influential the variables of entrepreneurship education, family environment and motivation on management student'entrepreneurial interest were. The method is a quantitative method. The population and sample in this study were all management students 2018-2022 as many as 128 people. The study resulted in an R coefficient of (0.717) and an Adjusted R Square coefficient of (0.503) this means that there is an influence of entrepreneurship education, family environment and motivation of (50.3%) and the rest (49.7%) is influenced by variables others not investigated. Entrepreneurship education has a positive and significant effect on management entrepreneurship interest, it is known that the t-count value is 2.961 which is greater than t-table of 1.979, family environment has a positive and significant effect on interest in management entrepreneurship. It is known that the t-count value is 6.991 which is greater than t- the table is 1.979, and motivation has a positive and significant effect on management's entrepreneurial interest, it is known that the t-count value of 4.661 is greater than the t-table of 1.979. Entrepreneurship education, family environment, motivation have a positive and significant influence on the entrepreneurial interest of management students, it is known that the fcount value of 43,772 is greater than ftable of 2.68, which is 43,772 > 2.68 with a significance level of 0.000. So Ho is rejected and Ha is accepted. In conclusion, entrepreneurship education, family environment and motivation in this study simultaneously and partially have a positive and significant effect on management students' entrepreneurial interest.